2022
DOI: 10.3390/ijms23158260
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Genomic Association Analysis Identifies the Candidate Genes Regulating Salt Tolerance in Cucumber (Cucumis sativus L.) Seedlings

Abstract: Salt stress seriously restricts plant growth and development, affects yield and quality, and thus becomes an urgent problem to be solved in cucumber stress resistance breeding. Mining salt tolerance genes and exploring the molecular mechanism of salt tolerance could accelerate the breeding of cucumber germplasm with excellent salt stress tolerance. In this study, 220 cucumber core accessions were used for Genome-Wide Association Studies (GWAS) and the identification of salt tolerance genes. The salinity injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Primer design was carried out using Primer 3.0 software (version 3; San Francisco, CA, USA) (Table 2). The qRT-PCR was operated with SYBR Green kit (Tiangen Biotech, Beijing, China), following the methods detailed by Liu et al [32]. Relative gene expression data analysis was performed using the 2 −∆∆Ct method [33].…”
Section: Rna Extraction and Qrt-pcr Verificationmentioning
confidence: 99%
“…Primer design was carried out using Primer 3.0 software (version 3; San Francisco, CA, USA) (Table 2). The qRT-PCR was operated with SYBR Green kit (Tiangen Biotech, Beijing, China), following the methods detailed by Liu et al [32]. Relative gene expression data analysis was performed using the 2 −∆∆Ct method [33].…”
Section: Rna Extraction and Qrt-pcr Verificationmentioning
confidence: 99%
“…(2019) detected five LT-tolerance loci ( gLTS1.1, gLTS3.1 , gLTS4.1 and gLTS5.1 ) on Chr.1, Chr.3, Chr.4 and Chr.5, respectively using low temperature injury indices. Seven loci ( gST2.1 , gST3.1 , gST4.1 , gST4.2, gST5.1, gST6.1) associated with salt tolerance in cucumber seedlings were repeatedly detected ( Liu et al., 2022a ). For quality traits, the ultra-high fruit spine density formation genes ( fsd6.2 ) ( Bo et al., 2019a ) and the green flesh formation gene ( qgf5.1 and qgf3.1 ) ( Bo et al., 2019b ) were identified using a group of 115 cucumber accessions from a core germplasm collection.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with molecular markers used in conventional gene/QTL mapping, genomic sequencing-based genotyping is a more convenient and effective alternative. Liu et al conducted Genome-Wide Association Studies (GWASs) by re-sequencing 220 cucumber core accessions and found that a total of seven loci were associated with salt tolerance in cucumber seedlings and finally predicted five candidate genes controlling salt tolerance [22].…”
mentioning
confidence: 99%